The Roman army and the New Testament - Zeichmann, Christopher B. (Lexington Books/Fortress Academic, 2018)
A war machine in the Holy Land?. - Who were the soldiers in Palestine?. - What did the military do in early Roman Palestine?. - The military in the Gospels and Acts. - The military in the Pauline corpus. - The military in Revelation. - Reading a complicated Bible in complicated times